2021
DOI: 10.1002/bit.27763
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and optimal design of batch and two‐column continuous chromatographic frontal processes for monoclonal antibody purification

Abstract: The increasing demand for efficient and robust processes in the purification of monoclonal antibodies (mAbs) has recently brought frontal chromatography to the forefront. Applied during the polishing step, it enables the removal of high molecular weight aggregates from the target product, achieving high purities. Typically, this process is operated in batch using a single column, which makes it intrinsically subjected to a purity‐yield tradeoff. This means that high purities can only be achieved at the cost of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Frontal chromatography occurs when the column is continuously loaded in which all of the components would then bind with the resin. It allows the product to have a high purity by removing large molecular weight aggregates from the intended product (Shi et al, 2021). Although it is not often employed for preparative scale purification of proteins, Hill et al (1990) as cited in Stone et al (2019) showed that it is possible to use frontal chromatography to purify the weakest interacting component in a combination preparative.…”
Section: Polishingmentioning
confidence: 99%
“…Frontal chromatography occurs when the column is continuously loaded in which all of the components would then bind with the resin. It allows the product to have a high purity by removing large molecular weight aggregates from the intended product (Shi et al, 2021). Although it is not often employed for preparative scale purification of proteins, Hill et al (1990) as cited in Stone et al (2019) showed that it is possible to use frontal chromatography to purify the weakest interacting component in a combination preparative.…”
Section: Polishingmentioning
confidence: 99%